The Importance of Cognitive and Social Skills for the Duration of Unemployment - Verena Niepel (Research Institute of Industrial Economics (IFN), 2011)
This paper studies how cognitive and social skills in childhood are related to the duration of unemployment in adolescence and early adulthood. I estimate a flexible proportional hazard rate model for the probability of making a transition from unemployment to employment during an individuals first unemployment spell. The analysis is based on British cohort data from the National Child Development Study. Results show that higher cognitive and social skills at the age of 7 are associated with an increased probability of finding employment, even when controlling for educational attainment. For men, these effects are mostly driven by individuals with low social skills. The results are robust to controlling for family background, parenting activities and school characteristics.
Keywords: C41; J24; J64; 330; Unemployment duration; Social skills; Noncognitive skills; Cognitive skills; Early skills; Arbeitslosigkeit; Dauer; Intelligenz; Soziale Kompetenz; Schätzung; Großbritannien